2012
DOI: 10.1029/2011jf002157
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic and climatic controls on knickpoint retreat rates and landscape response times

Abstract: [1] The rate at which transient knickpoints propagate through a landscape fundamentally controls the rate of geomorphic response to tectonic and climatic perturbation. Here we present knickpoint retreat rates upstream of active faults for 19 bedrock catchments in Turkey and 11 bedrock catchments in Italy where we have very good constraints on both the magnitude and timing of the tectonic perturbation and where climate histories are well documented. We show that the knickpoints have average retreat rates of bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
254
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 189 publications
(277 citation statements)
references
References 90 publications
(305 reference statements)
21
254
0
2
Order By: Relevance
“…10). Our results are also consistent with the field-based findings of Whittaker and Boulton (2012), who showed that landscape response times for rivers close to the detachment-limited end-member were shorter for terrain uplifted by faster-slipping active faults. Figure 13.…”
Section: Non-linear Response Timescalessupporting
confidence: 92%
See 3 more Smart Citations
“…10). Our results are also consistent with the field-based findings of Whittaker and Boulton (2012), who showed that landscape response times for rivers close to the detachment-limited end-member were shorter for terrain uplifted by faster-slipping active faults. Figure 13.…”
Section: Non-linear Response Timescalessupporting
confidence: 92%
“…Taking the drainage length to be directly proportional to the catchment area, l d ∝ a, and given that catchment length is proportional to drainage area raised to the Hack exponent, h, we can re-write Eq. (14) as Therefore, in the case that h = 0.5 and m = 0.5, as in the numerical model here, the response time becomes independent of system length (see Whittaker and Boulton, 2012). If h < m then response times would decrease with increasing drainage basin size, and if h > m then response times would increase with drainage basin size.…”
Section: Response To Different Magnitudes Of Precipitation Rate Changementioning
confidence: 74%
See 2 more Smart Citations
“…However, possibly because the control of K on steepness is damped by sorting and attrition effects on bedload grain size with distance, the lower segments of the I<rios and Trikalitikos do not show the low steepness expected from their lithological conditions. This not only confirms the minor role of bedrock resistance to erosion in the long-term process of river incision (Roberts and White, 2010;Whittaker and Boulton, 2012;Beckers et al, 2014), but also shows that, except in the far west of the study area, the current episode of uplift is more intense than the previous one.…”
Section: Steepnesssupporting
confidence: 73%